Smes in an era of globalization : international business and market strategies. - Bijaoui, Ilan (Palgrave Macmillan, 2016)
This book identifies the driving forces behind globalization and proposes innovative ways for small and medium enterprises to confront them. More than ever, sustainable competitive advantage requires SMEs to continually adapt their strategy and confront new and current competition in the international market. SMEs working with multinational companies could also benefit from winning strategies based on a sensible analysis of rational and irrational phenomena at the micro- and macro-economic levels. This book uses different models developed and established through international business experiences to determine innovative ways to navigate today's global landscape. It illustrates each model through real, successful case studies of globalization of factor, efficiency, and innovation-driven SMEs. It will benefit scholars of entrepreneurship, international business, regional development as well as managers, governmental institutions, and regional development, and consultants to SMEs. Ilan Bijaoui is Senior Lecturer in the School of Business Management at Bar-Ilan University, Israel, teaching courses across marketing, international business, and innovation strategy. He serves as lecturer and consultant for international organization and the Israeli Ministries of Economics, Agriculture, and Foreign Affairs. He has written numerous articles in top business and economic journals and is the author of The Economic Reconciliation Process and The Open Incubator Model (Palgrave Macmillan).- Resumé vydavatel
Keywords: podnikání; marketing; nadnárodní společnosti; globalizace; business; globalization; international business enterprises; elektronické knihy; monografie; electronic books; monographs